The Civic Dimension of School Voucher Programs. (3rd March 2020) - Merritt, Cullen C.; Suess Kennedy, Sheila; Farnworth, Morgan D.
Abstract : America's public schools have not been exempt from the movement to privatization and contracting out that has characterized government innovations over at least the past quarter century. A number of the issues raised by school voucher programs mirror the management and efficacy questions raised by privatization generally. However, because public education is often said to be "constitutive of the public, " using tax dollars to send the nation's children to private schools implicates the distinctive role of public education in a democratic society in ways that more traditional contracting arrangements do not. By using a content analysis, the authors explore the extent to which school choice voucher programs are mandated by state statutes to integrate civics education into their curriculum. Findings reveal that across the 14 states (and the District of Columbia) that have enacted school choice voucher programs, statutes exempt these programs from curriculum oversight, including civics requirements, and grant them considerable autonomy in designing their curricula. This study concludes by discussing the implications for ethical and accountable governance when primary and secondary schools fail to cultivate civic competence and civic literacy.